Related Factors to Exclusive Breastfeeding in Puskesmas Ketaping of Padang Pariaman District - Hega Valentine (JUMP Health (Journal of Ultimate Public Health), 2018)
Exclusive breastfeeding means infantsare only breastfed without anyother additional foods, neither fluids or solids, as it is the best food for babies because it contains a complete and perfect nutrients and also supplies antibodies and anti-infective substances that can prevent them from various diseases. The purpose of this study was to determine the factors associated with The Exclusive Breastfeeding in the work area of Puskesmas Ketaping Padang Pariaman. This study used survey method with cross sectional study design with infant population aged 4 to 12 months. The sample size is 93 babies’ mothers. The study was conducted from 15th to 25thof August in 2004 by using a quessioner. After data had been collected and then manually processed and computerized, then it was presented in the distribution table and cross table and used a statistical tests (Chi-Square). The results showed that the level of knowledge, education, employment status and support from the babies’ mothers’ families is quite low, less than 50%. And there is a significant relationship between knowledge and the Exclusive Breastfeeding (p = 0,01), education with the Exclusive Breastfeeding (p = 0,04), work status with the Exclusive Breastfeeding (p = 0,01), and family support with the Exclusive Breastfeeding (p = 0.01). So thatthese infant’s mother need intensively to be counseled and approached in family leveland so as the cooperation from the officers in the In the information delivery about The Exclusive Breastfeeding.